The opinions of the pre-service teachers about e-democracy in Turkey - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
Today, Internet has a widespread position in the world and the usage of electronic environments in the context of governance was begun. Because of the important role of e-democracy processes in 21(st) century and importance of the social studies pre-service teachers in training active citizens, in this study opinions of the social studies pre-service teachers about e-democracy are presented. The data has been collected from pre-service teachers through interviews. The data has been collected from pre-service teachers through interviews. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Citizenship; e-democracy; governmental web-sites